TWO WAYS OF IMPLEMENTING LANGUAGE EDUCATION POLICY: TOP-DOWN AND BOTTOM-UP: A REVIEW OF A CASE STUDY (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
The English language takes an important place in university teaching, most literature as well as publications from the SCI (Science Citation Index) list are written in English, and knowledge of that foreign language is considered an important qualification that academic citizens should have, since it gives them the opportunity to get involved in international flows. For that reason, this paper presents a case study of the implementation of language education policy at the Faculty of Agriculture in Krusevac, University of Nis. It is important to emphasize that the aim of the paper is not to show which way of implementing language education policies is better, but to provide insight into the ways they function.
Keywords: language education policy; language policy and planning; foreign language teaching; English language; higher education